TABANNI SEBAGAI HALUAN GERAKAN HIZBUT TAHRIR INDONESIA - Arif Gunawan Santoso (Harmoni, 2015)
Nowadays, it is found a negative stigma facing Islamic fundamentalism. However Indonesian Hizbut Tahrir (HTI) still exists and has strong influence. This organization is different from the others. It does not have regional or national figures. This research applies quantitative approach and has purpose to discover the factors that increase its influences despite having negative stigma and rejection. Framing theory is conducted to analyze the data and result. The result shows that HTI is not same with the other organizations that have leaders to drive their followers. HTI emphasizes on the tabanni idea and thought to drive their followers.